Effects of temperature on viscosity, stability, and microstructure of water-in-biodiesel microemulsions - Ashikhmin A. E. Alexander Evgenjevich; Andropov M. O. Mikhail Olegovich; Piskunov M. V. Maksim Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Yanovsky V. A. Vyacheslav Aleksandrovich (2023, 2023)
Title screen